Principals' Managerial Strategies in Integrating IQ, EQ, and SQ in Islamic Early Childhood Education - Astuti Darmiyanti; Vismaia Nur Fitriani (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This study aims to examine the managerial strategies of school principals in integrating intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) to optimize the growth and development of early childhood in Islamic early childhood education institutions. The integration of these three dimensions of intelligence is important because early childhood development emphasizes not only cognitive aspects, but also character building, emotional management, and the internalization of spiritual values. This study uses a qualitative, multi-site case study design conducted across three Islamic kindergartens in Karawang Regency. The multi-site design was chosen to obtain a more comprehensive understanding of variations in managerial strategies across institutions. Research data were obtained through questionnaires distributed to school principals and teachers, comprising closed- and open-ended questions to explore managerial planning, implementation, supervision, and evaluation practices in the development of children's holistic intelligence. The data were analyzed descriptively and thematically to identify patterns of managerial strategies applied at each research location. The results showed that principals applied integrative strategies by implementing holistic learning planning, strengthening teacher collaboration, structuring task-sharing, and instilling religious values in daily learning activities. These strategies support the balanced development of children in cognitive, social-emotional, and spiritual aspects. However, this study also found several obstacles, including limited teacher competence, limited learning time, and variations in parental support. This study recommends strengthening teacher professional development, increasing synergy between schools and parents, and strengthening integrative management to improve the quality of Islamic early childhood education.